Perceraian Sepihak oleh Suami Tanpa Sepengetahuan Istri dalam Perspektif Hukum Acara Peradilan Agama - Nurmala Dewi; Lia Ramadani; Nessy Pradinata; Jefri Buchori; Muhammad Guntur (Media Hukum Indonesia (MHI), 2026)
This study aims to examine the legal standing of unilateral divorce initiated by a husband without the wife's knowledge within the context of religious court procedural law in Indonesia. The background of this study is a recurring societal phenomenon where husbands pronounce talaq (repudiation) outside the court or conceal the divorce process from their wives with the intention of remarrying. This research employs a normative juridical approach with qualitative data derived from secondary sources, including statutory regulations, court decisions, the Compilation of Islamic Law (KHI), and Islamic family law literature. Data were analyzed using descriptive-qualitative methods. The results indicate that a divorce conducted by a husband without his wife's knowledge and without going through a religious court session is legally invalid under Indonesian positive law. A husband who divorces his wife outside the court to remarry may face sanctions, including the rejection of a new marriage registration, a lawsuit for marriage annulment, and claims for the rights of the wife and children. Legal protection for wives in religious court procedural law is both preventive and repressive, implemented through mechanisms of summons, mediation, and fair, open court proceedings.